Islamic Political Identity in Turkey: By M. Hakan Yavuz (USA: Oxford University Press, 2003. 328 pages.) (American Journal of Islam and Society, 2005)
During the events that led to the “soft coup” of the Erbakan-Çiller coalitiongovernment in 1997, the Turkish military declared that the number onethreat to national security was not Kurdish separatism, but Islamic radicalism.Despite this shift in security strategy, the Justice and Developmentparty, which was born from the ashes of Erbakan’s openly Islamist Refahparty, won a decisive victory at the polls in November 2002. These seriesof events from Turkey’s recent history have raised many questions in theminds of observers, both international and domestic, as to the nature andstrength of Islamic political and social movements in the Republic ofTurkey – a state that since its birth in 1923 had undergone a systematic programof westernization and secularization.In his Islamic Political Identity in Turkey, M. Hakan Yavuz attempts toanswer these very questions by providing a comprehensive analysis of themain Muslim social groups that have come to dominate Turkish-Muslimsociety, namely, the Nakshibendi Sufi orders and the Nurcu movement.These groups have made significant inroads into Turkish civil society, crossingclass, regional, and ethnic lines, by taking advantage of new opportunityspaces in the market, the print media, and education. This was a directresult of the political and economic liberalization policies of the Özal governmentduring the 1980s.As the author argues, “the secularizing, state-centric elite failed effectivelyto penetrate and transform traditional society, and was similarlyunsuccessful in developing an alternative value system and associational lifefor the rural population of society” (p. 4). Thus, the social and ethical vacuumcreated by the Kemalists was appropriated by a diverse group of Islamicsocial movements that were then urbanized by way of the gecekondus, theshanty-towns built overnight by rural migrants to the big cities during the1960s and 1970s. These movements, which were silently germinating in theAnatolian countryside, underwent what Yavuz aptly terms the “vernacularization ...